Aboriginal People and Labour Relations - Morse, Brad (Revue générale de droit)

(untitled) (Éditions de l’Université d’Ottawa, 1986)
The original inhabitants of Canada (the Indian, Inuit and Metis peoples) now number approximately one million people. Although they represent only about 4% of the national population, they are a significant force in the Canadian economy. It is, thus, rather surprising to note the limited attention that aboriginal communities and aboriginal workers have received from the trade union movement.There is currently an active movement for the restoration of self-government and self-determination for aboriginal peoples in accordance with their own laws through a constitutionally mandated process and by way of direct negotiations with federal and provincial governments. Developments in this regard will clearly impact on labour relations. This essay attempts to provide a brief review of the present state of labour law as it relates to the aboriginal peoples of Canada, to serve as a foundation on which change may be built.